Research trends on nanomaterials in gastric cancer: a bibliometric analysis from 2004 to 2023 - Ling, Li-Xiang; Ouyang, Yaobin; Hu, Yi (Journal of nanobiotechnology, 2023)
Gastric cancer is one of the leading causes of cancer-related deaths worldwide. In recent years, an increasing number of studies aimed at designing and developing nanomaterials for use in diagnosing and treating gastric cancer have been conducted. In this study, we aimed to comprehensively assess the current status and trends of the research on the application of nanomaterials in gastric cancer through a bibliometric analysis. Studies focusing on nanomaterials and gastric cancer were retrieved from the Web of Science Core Collection database and relevant articles were selected for inclusion in the study according to the inclusion criteria. Bibliometric and visual analysis of the included publications was performed using VOSviewer and CiteSpace. A total of 793 studies were included. An increase in annual publications was observed from 2004 to 2023. China, Iran and the USA were the dominant countries in this field, accounting for 66.1%, 11.5% and 7.2% of publications, respectively. Shanghai Jiao Tong University and Cui DX were the most influential institution and author, respectively. The International Journal of Nanomedicine was the most prolific journal; Biomaterials was the most cited and most cocited journal. Nanomaterial-related drug delivery and anticancer mechanisms were found to be the most widely researched aspects, and green synthesis and anticancer mechanisms are recent research hotspots. In this study, we summarized the characteristics of publications and identified the most influential countries, institutions, authors, journals, hot topics and trends regarding the application of nanomaterials in gastric cancer.